A high-conductivity slurry with low conductive phase filling amount and preparation method thereof

By using the cross-linking curing technology of polyo-epoxy-N-methylaniline conductive adhesive resin, polybenzine curing agent and organic macromolecular protonic acid, the existing conductive paste has solved the problem of high hardness, high brittleness and high resistance. The problem of this method is to achieve high conductivity and excellent film forming slurry, which is suitable for applications of smaller and intelligent components.

CN114613528BActive Publication Date: 2025-02-18NANJING UNIV OF TECH OPTOELECTRONIC MATERIALS RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210246877.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-09
Publication Date
2025-02-18
Estimated Expiration
2042-03-09

AI Technical Summary

Technical Problem

The existing conductive paste has problems such as high hardness, high brittleness and high resistance of the printed film layer, which is difficult to meet the needs of smaller and intelligent components.

Method used

Polyo-epoxy-N-methylaniline conductive adhesive resin is used as the binder, and the cross-linking is cured with a polybenzine curing agent and an organic macromolecular proton acid to form a conductive conductivity with high conductivity and excellent film formation. Organic thermosetting material.

Benefits of technology

It has achieved high conductive slurry with high conductivity with high conductivity and excellent thermal oxidation resistance, ultraviolet resistance, film formation and adhesive properties, significantly improving the conductive properties of the slurry and low-temperature curing film formation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-conductivity slurry with a low conductive phase filling amount and a preparation method thereof. The slurry comprises 30-40% of a poly-o-epoxy-N-methylaniline conductive organic carrier and 60-70% of silver powder by mass percentage; the poly-o-epoxy-N-methylaniline conductive organic carrier comprises the following components by mass percentage: 20-25% of a poly-o-epoxy-N-methylaniline conductive adhesive resin, 1-3% of a polybenzidine curing agent, 70-75% of a solvent, and 1-2% of an auxiliary agent. The conductive organic carrier and the silver powder are compounded to form a highly conductive slurry, and the conductive organic carrier plays a bonding role in the slurry while assisting the silver powder to form a conductive network, so that the purpose of achieving high conductivity with a low conductive phase filling amount can be achieved; the slurry of the invention has the low-temperature curing performance of the conductive organic carrier, significantly improves the conductive performance, low-temperature curing film-forming performance and anti-aging performance of the slurry, and can improve the reliability of the high-conductivity slurry application product.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention patent application is a divisional application. The name of the invention of the original application is: a poly-o-epoxy-N-methylaniline conductive adhesive resin and preparation method, conductive organic thermosetting material and application; the application date is: March 9, 2022; the application number is 2022102315528. Technical Field

[0002] The present invention relates to a bonding resin and a preparation method thereof, an organic carrier and a preparation method thereof, a conductive organic thermosetting material and an application thereof, a conductive paste and a preparation method thereof, and in particular to a poly-o-epoxy-N-methylaniline conductive bonding resin and a preparation method thereof, a conductive organic thermosetting material and an application thereof, a poly-o-epoxy-N-methylaniline conductive organic carrier and a preparation method thereof, and a highly conductive paste with a low conductive phase filling amount and a preparation method thereof. Background Art

[0003] The resistivity of conductive polymers is generally around 10 -1 ~10 -2 Ω·cm, among which typical ones are conjugated polymers with aromatic heterocycles as basic structural units, such as polyaniline, polypyrrole and polythiophene. In particular, polyaniline has a simple synthesis process, is non-toxic, and has low raw material prices. It has been widely used in electrocatalysis, electroanalytical chemistry, and functional electronic devices. However, the intermolecular hydrogen bonds between the aromatic rings and the amine and imine groups of polyaniline make it almost insoluble in any solvent, and its solubility and rheological properties are not conducive to processing and molding.

[0004] Structural modification and modification of polyaniline is one of the effective ways to solve the problem of polymer solubility and processability. The introduction of substituents can reduce the coplanarity of the molecular chain and the rigidity of the macromolecular main chain, and the dilution effect of the group weakens the interaction between the macromolecular chains, thereby improving solubility. The use of macromolecular proton acids for doping, its soluble long-chain end groups, etc. improve the compatibility between the polymer and the solvent. The modified polyaniline reported so far is mainly based on linear structures, and the mechanical strength of the prepared conductive layer and the bonding strength with the substrate are poor, which limits its application in many fields such as electronic circuits, solar photovoltaic panels, electromagnetic shielding, and electronic devices.

[0005] Conductive paste is the basis for the development of electronic components. It is usually printed on substrates to enable them to conduct current. It consists of two parts: a conductive phase and an organic carrier. The conductive phase is mainly silver powder, and the organic carrier is mainly composed of a binder, a viscosity-reducing solvent, and an additive. The high-speed transmission, miniaturization, and intelligent development trend of the electronic information industry require that the conductive paste used in the components have higher conductivity, higher printing fine resolution, and uniformity.

[0006] The binder is a film-forming substance in the conductive paste, usually a resin organic compound. Its type, content, molecular weight, etc. have a great influence on the paste's properties such as bending resistance, hardness, adhesion and printability.

[0007] At present, the conductive paste on the market often uses insulating polymer materials such as epoxy resin, phenolic resin, acrylic resin as a binder. The conductive paste of this system has the problems of high hardness, high brittleness and high resistance (generally the volume resistivity is 10 -4 ~10 -5 Ω·cm) and other issues. Since the insulating polymer binder is non-conductive, the cured resin will coat the surface of the conductive phase particles and even block the transmission of electrons. If the insulating resin is used as a binder, a more reliable conductive paste cannot be obtained for use in more miniaturized and intelligent components. Summary of the invention

[0008] Purpose of the invention: The purpose of the present invention is to provide a highly conductive slurry with good conductivity and strong adhesion and low conductive phase filling amount;

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned high conductive paste with a low conductive phase filling amount.

[0010] Technical solution: The poly-o-epoxy-N-methylaniline conductive adhesive resin of the present invention has a structural monomer of:

[0011]

[0012] Here, x is a positive integer between 10 and 200.

[0013] The preparation method of the above-mentioned poly-o-epoxy-N-methylaniline conductive adhesive resin comprises the following steps:

[0014] (1) Under an inert atmosphere, N-methylaniline and persulfate are placed in a hydrochloric acid aqueous solution for polymerization reaction to obtain a proposed N-methylaniline polymer; after washing and drying, the polymer is treated with ammonia water to obtain an intrinsic state N-methylaniline polymer;

[0015] (2) dissolving the intrinsic N-methylaniline polymer in a good solvent, adding a halogenated epoxide, and coupling the epoxy group to the aromatic ring of the N-methylaniline polymer under the action of a catalyst to obtain an ortho-epoxy-N-methylaniline binder resin solution; filtering to remove the catalyst, and removing the solvent to obtain the product.

[0016] The synthetic route of the above-mentioned ortho-epoxy-N-methylaniline bonding resin is as follows:

[0017]

[0018] Wherein, in step (1), the polymerization time is 3 to 10 hours, and the polymerization temperature is 40 to 80°C.

[0019] Wherein, in step (2), the ratio of the epoxy group to the aromatic ring is 1:2 to 10; the catalyst is 0.05 to 0.1 g / mL of anhydrous AlCl3; the concentration of the intrinsic N-methylaniline polymer is 0.05 to 0.5 g / mL, and the concentration of the halogenated epoxide is 0.02 to 0.1 g / mL; and the good solvent is at least one of acetone, butanone, DMF, DMSO, pyridine or N-methylpyrrolidone.

[0020] The poly-o-epoxy-N-methylaniline conductive organic thermosetting material of the present invention is prepared by mixing the above-mentioned o-epoxy-N-methylaniline bonding resin with a polybenzidine curing agent and a dopant and then curing the mixture through cross-linking.

[0021] Wherein, the dopant is an organic macromolecular protonic acid; the organic macromolecular protonic acid is dodecylbenzenesulfonic acid and / or dodecylsulfonic acid.

[0022] Wherein, the mass ratio of the o-epoxy-N-methylaniline bonding resin, the polyphenylamine curing agent and the dopant is 100:1-5:5-20.

[0023] Wherein, the polymerization degree of the polyphenylamine curing agent is 3-5.

[0024] The above-mentioned poly-o-epoxy-N-methylaniline conductive organic thermosetting material is used in a conductive film; specifically, the poly-o-epoxy-N-methylaniline conductive organic thermosetting material is coated on the surface of a base material, and after the solvent evaporates, it is cured into a film at a certain temperature to obtain a poly-o-epoxy-N-methylaniline thermosetting conductive film; the curing film temperature is preferably 120°C-150°C; more preferably 140°C-150°C.

[0025] The polyaniline curing agent can not only cross-link and cure with the epoxy groups on the o-epoxy-N-methylaniline binder resin, but also undergo secondary coupling with the end groups of the o-epoxy-N-methylaniline binder resin to form a bulk structured polyaniline. At the same time, after being doped with a dopant, carriers are introduced to form a three-dimensional network conductive path.

[0026] A poly-o-epoxy-N-methylaniline conductive organic carrier comprises the following components by mass percentage: 20-25% of the poly-o-epoxy-N-methylaniline conductive adhesive resin, 1-3% of a polybenzidine curing agent, 70-75% of a solvent and 1-2% of an auxiliary agent.

[0027] Wherein, the solvent is at least one of isophorone, butyl carbitol acetate or butyl carbitol; the auxiliary agent is preferably a thixotropic agent, and the thixotropic agent is preferably an organic gel in patent CN109473197.

[0028] The method for preparing the above-mentioned poly-o-epoxy-N-methylaniline conductive organic carrier comprises the following steps:

[0029] The invention is prepared by mixing, grinding, defoaming and degassing poly-o-epoxy-N-methylaniline adhesive resin, polybenzidine curing agent, organic macromolecular protonic acid, solvent and auxiliary agent according to mass percentage.

[0030] After mixing, the temperature is raised to 70-100° C. and stirred at the constant temperature for 2-4 hours.

[0031] A high-conductivity paste with a low conductive phase filling amount comprises, by mass percentage, 30-40% of the above-mentioned poly-o-epoxy-N-methylaniline conductive organic carrier and 60-70% of silver powder; the poly-o-epoxy-N-methylaniline conductive organic carrier comprises, by mass percentage, the following components: 20-25% of poly-o-epoxy-N-methylaniline conductive adhesive resin, 1-3% of polybenzidine curing agent, 70-75% of solvent and 1-2% of auxiliary agent.

[0032] The preparation method of the high conductive paste with low conductive phase filling amount is as follows:

[0033] The poly-o-epoxy-N-methylaniline bonding resin, polybenzidine curing agent, solvent and auxiliary agent are mixed according to mass ratio, and then mixed with silver powder after defoaming and degassing to obtain the product.

[0034] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0035] (1) The o-epoxy-N-methylaniline adhesive resin of the present invention has excellent conductivity, solubility and film-forming properties. (2) The poly-o-epoxy-N-methylaniline conductive organic thermosetting material has excellent thermal oxidation resistance and UV resistance; (3) The poly-o-epoxy-N-methylaniline conductive organic thermosetting material has good conductivity. (4) The poly-o-epoxy-N-methylaniline conductive organic thermosetting material has excellent film-forming and bonding properties. (5) In the conductive organic carrier of the present invention, polyphenylamine and adhesive resin are mixed, and the amine NH on the polyphenylamine reacts with the epoxy group on the adhesive resin to achieve curing. At the same time, the polyphenylamine and the adhesive resin undergo a coupling reaction to form an integral conductive network structure. The conductive organic carrier formed after mixing with a solvent and an additive has high conductivity and strong bonding properties. (6) The conductive organic carrier of the present invention is compounded with silver powder to form a highly conductive slurry. The conductive organic carrier plays a bonding role in the slurry and assists the silver powder in forming a conductive network, which can achieve the purpose of achieving high conductivity with a low conductive phase filling amount. In addition, the slurry of the present invention has the low-temperature curing performance of a conductive organic carrier, which significantly improves the conductive performance, low-temperature curing film-forming performance and anti-aging performance of the slurry, and can improve the reliability of high-conductivity slurry application products. DETAILED DESCRIPTION

[0036] The present invention is described in further detail below.

[0037] Example 1

[0038] A method for preparing a poly-o-epoxy-N-methylaniline conductive adhesive resin comprises the following steps:

[0039] (1) Under an inert atmosphere, N-methylaniline and (NH4)2S2O2 are placed in a hydrochloric acid aqueous solution for polymerization reaction, and the polymerization time is controlled to be 4 hours to obtain an N-methylaniline polymer with an average degree of polymerization of 50;

[0040] (2) washing the obtained N-methylaniline polymer precipitate with deionized water, drying it at 80° C. for 12 h, and then treating it with ammonia water to obtain an intrinsic N-methylaniline polymer;

[0041] (3) Prepare an intrinsic N-methylaniline polymer with a solubility of 0.1 g / mL and dissolve it in DMF, add 0.05 g / mL epichlorohydrin and 0.05 g / mL anhydrous AlCl3, and perform a coupling reaction at a polymerization temperature of 60°C for 8 hours. Then, filter to remove the anhydrous AlCl3 catalyst and remove the solvent to obtain a poly-o-epoxy-N-methylaniline binder resin with a ratio of epoxy groups to aromatic rings of about 1:4.

[0042] The resistivity test found that the conductivity and yield of N-methylaniline polymer increased with the increase of oxidant concentration. When the oxidant concentration was greater than 1.0 M, the yield and yield decreased. The infrared spectrum of N-methylaniline polymer found that N-methylaniline polymer was a 1,4-linked head-to-tail structure, in which the quinone structure (1590 cm -1 ) intensity relative to the benzene structure (1500cm -1 ), and it increases with the increase of oxidant concentration, that is, increasing the oxidant concentration can increase the proportion of quinone structure, which is beneficial to the increase of conductivity.

[0043] In addition, through solubility analysis, the intrinsic and doped N-methylaniline polymers can be dissolved in solvents such as DMF, DMSO, pyridine and N-methylpyrrolidone.

[0044] According to the thermogravimetric diagram of N-methylaniline polymer in air, it can be seen that N-methylaniline polymer begins to decompose at around 320°C, indicating that it has good thermal stability.

[0045] The doped N-methylaniline polymer has a certain environmental stability. After being placed in the air for half a year, the conductivity increases from 8×10 -3 S / cm becomes 1.0×10 -2 S / cm.

[0046] The doped N-methylaniline polymer was dissolved in chloroform solution, showing good film-forming properties. The epoxy group substitution on the benzene ring of the N-methylaniline polymer can maintain its excellent conductivity while improving its adhesion and solubility in various solvents such as DMF and acetone.

[0047] Example 2

[0048] A method for preparing a poly-o-epoxy-N-methylaniline conductive adhesive resin comprises the following steps:

[0049] (1) Under an inert atmosphere, N-methylaniline and (NH4)2S2O2 are placed in a hydrochloric acid aqueous solution for polymerization reaction, and the polymerization time is controlled to be 6 hours to obtain an N-methylaniline polymer with an average degree of polymerization of 100;

[0050] (2) washing the obtained N-methylaniline polymer precipitate with deionized water, drying it at 80° C. for 12 h, and then treating it with ammonia water to obtain an intrinsic N-methylaniline polymer;

[0051] (3) Prepare an intrinsic N-methylaniline polymer with a solubility of 0.4 g / mL and dissolve it in acetone, add 0.1 g / mL epichlorohydrin and 0.05 g / mL anhydrous AlCl3, and perform a coupling reaction at a polymerization temperature of 40°C for 5 hours. Then, filter to remove the anhydrous AlCl3 catalyst and remove the solvent to obtain a poly-o-epoxy-N-methylaniline binder resin with a ratio of epoxy groups to aromatic rings of about 1:8.

[0052] Example 3

[0053] Based on Example 1, the difference from Example 1 is that in step (3), the solubility of the intrinsic N-methylaniline polymer is 0.05 g / mL, epichlorohydrin is 0.02 g / mL, anhydrous AlCl3 is 1 g / mL, and the ratio of epoxy group to aromatic ring is about 1:2.

[0054] Example 4

[0055] Based on Example 1, the difference from Example 1 is that in step (3), the solubility of the intrinsic N-methylaniline polymer is 0.5 g / mL, and the ratio of epoxy groups to aromatic rings is about 1:10.

[0056] Example 5

[0057] The poly-o-epoxy-N-methylaniline prepolymer of Example 1 was dissolved in acetone, and 5% of dodecyl sulfonic acid relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, and 5% of a polyphenylamine curing agent with a polymerization degree of 5 relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, mixed evenly, and coated on the surface of the substrate material. After the solvent evaporated, it was cured at 150° C. to form a film, thereby obtaining a poly-o-epoxy-N-methylaniline thermosetting conductive film with a volume resistivity of 10 ± 2Ω·cm.

[0058] Example 6

[0059] The poly-o-epoxy-N-methylaniline prepolymer of Example 2 was dissolved in acetone, 3% of dodecyl sulfonic acid relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, and 10% of a polyphenylamine curing agent with a polymerization degree of 3 relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, mixed evenly, and coated on the surface of the substrate material. After the solvent evaporated, it was cured at 140° C. to form a film, and a volume resistivity of 10 was obtained. 2 ±10Ω·cm poly-o-epoxy-N-methylaniline thermosetting conductive film.

[0060] Example 7

[0061] The poly-o-epoxy-N-methylaniline prepolymer of Example 1 was dissolved in acetone, and 2% of dodecyl sulfonic acid relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, and 15% of a polyphenylamine curing agent with a polymerization degree of 3 relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added. The mixture was evenly mixed, and coated on the surface of the substrate material. After the solvent evaporated, the film was cured at 140° C. to obtain a volume resistivity of 10 3 ±50Ω·cm poly-o-epoxy-N-methylaniline thermosetting conductive film.

[0062] Example 8

[0063] The poly-o-epoxy-N-methylaniline prepolymer of Example 1 was dissolved in acetone, 1% of dodecyl sulfonic acid relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, and 20% of a polyphenylamine curing agent with a polymerization degree of 3 relative to the mass of the poly-o-epoxy-N-methylaniline prepolymer was added, mixed evenly, and coated on the surface of the substrate material. After the solvent evaporated, it was cured at 140° C. to form a film, and a volume resistivity of 10 4 ±500Ω·cm poly-o-epoxy-N-methylaniline thermosetting conductive film.

[0064] Example 9

[0065] The poly-o-epoxy-N-methylaniline binder resin of Example 3 is mixed with a polyphenylamine curing agent, a solvent, and an auxiliary agent according to a mass ratio, and the temperature is raised to 70°C. After constant temperature stirring for 4 hours, the material is cooled and tested to obtain a slurry mixture; then, after defoaming and degassing, a poly-o-epoxy-N-methylaniline conductive organic carrier is obtained. Among them, the solvent is a mixed solvent composed of isophorone, butyl carbitol acetate, and butyl carbitol, and the auxiliary agent is an organic gel in patent CN109473197. The specific ratios of each component are shown in Table 1.

[0066] Example 10

[0067] The poly-o-epoxy-N-methylaniline binder resin of Example 4 is mixed with a polyphenylamine curing agent, a solvent, and an auxiliary agent according to a mass ratio, and the temperature is raised to 85°C. After constant temperature stirring for 3 hours, the material is cooled and tested to obtain a slurry mixture; then, after defoaming and degassing, a poly-o-epoxy-N-methylaniline conductive organic carrier is obtained. Among them, the solvent is a mixed solvent composed of isophorone, butyl carbitol acetate, and butyl carbitol, and the auxiliary agent is an organic gel in patent CN109473197. The specific ratios of each component are shown in Table 1.

[0068] Embodiment 11

[0069] The poly-o-epoxy-N-methylaniline binder resin of Example 1 is mixed with a polyphenylamine curing agent, a solvent, and an auxiliary agent according to a mass ratio, and the temperature is raised to 100°C. After constant temperature stirring for 2 hours, the material is cooled and tested to obtain a slurry mixture; then, after defoaming and degassing, a poly-o-epoxy-N-methylaniline conductive organic carrier is obtained. Among them, the solvent is a mixed solvent composed of isophorone, butyl carbitol acetate, and butyl carbitol, and the auxiliary agent is an organic gel in patent CN109473197. The specific ratios of each component are shown in Table 1.

[0070] Example 12

[0071] A high-conductivity paste with a low conductive phase filling amount comprises, by mass percentage, 30% of the poly-o-epoxy-N-methylaniline conductive organic carrier of Example 9 and 70% of silver powder.

[0072] The silver powder of this embodiment has a particle size of 0.8-1.2 μm and a tap density of 3.2-3.8 g / ml.

[0073] The method for preparing the highly conductive paste with a low conductive phase filling amount comprises the following steps: mixing the poly-o-epoxy-N-methylaniline conductive organic carrier of Example 9 with silver powder according to a mass ratio, and grinding with a three-roll mill to obtain a highly conductive paste with a fineness of less than 5 μm.

[0074] Example 13

[0075] A high-conductivity paste with a low conductive phase filling amount comprises, by mass percentage, 35% of the poly-o-epoxy-N-methylaniline conductive organic carrier of Example 9 and 65% of silver powder.

[0076] The silver powder of this embodiment has a particle size of 0.8-1.2 μm and a tap density of 3.2-3.8 g / ml.

[0077] The method for preparing the highly conductive paste with a low conductive phase filling amount comprises the following steps: mixing the poly-o-epoxy-N-methylaniline conductive organic carrier of Example 9 with silver powder according to a mass ratio, and grinding with a three-roll mill to obtain a highly conductive paste with a fineness of less than 5 μm.

[0078] Embodiment 14

[0079] A high-conductivity paste with a low conductive phase filling amount comprises, by mass percentage, 40% of the poly-o-epoxy-N-methylaniline conductive organic carrier of Example 9 and 60% of silver powder.

[0080] The silver powder of this embodiment has a particle size of 0.8-1.2 μm and a tap density of 3.2-3.8 g / ml.

[0081] The method for preparing the highly conductive paste with a low conductive phase filling amount comprises the following steps: mixing the poly-o-epoxy-N-methylaniline conductive organic carrier of Example 9 with silver powder according to a mass ratio, and grinding with a three-roll mill to obtain a highly conductive paste with a fineness of less than 5 μm.

[0082] The test results of the slurry properties of Examples 12-14 are shown in Table 2 below.

[0083] Table 1 Poly-o-epoxy-N-methylaniline conductive organic carrier formulations of Examples 9 to 11

[0084]

[0085] Table 2 Slurry performance test results of Examples 12-14

[0086] serial number Volume resistivity (Ω·cm) Bending resistance / resistance change rate Weather resistance Example 12 <![CDATA[6.7*10 -6 ]]> No abnormality / ≤10% No discoloration, no peeling Example 13 <![CDATA[5.3*10 -6 ]]> No abnormality / ≤10% No discoloration, no peeling Embodiment 14 <![CDATA[4.7*10 -6 ]]> No abnormality / ≤10% No discoloration, no peeling

[0087] It can be seen from the data in Table 2 that the paste using a conductive organic carrier has lower volume resistivity, high conductivity and good printability while reducing the amount of silver powder used.

[0088] In Table 2, the bending resistance test method is: using a cylindrical mandrel method with a diameter of 1mm to confirm cracks and resistance change rate. The weather resistance test method is: using a weather resistance acceleration tester, the black panel temperature is 85+ / -1℃, 85%+ / -1% humidity for 1000 hours, and observe whether there is discoloration and peeling.

Claims

1. A highly conductive slurry with a low conductive phase filling amount, characterized in that: The poly-o-epoxy-N-methylaniline conductive organic carrier comprises 30-40% and silver powder 60-70% by mass percentage; the poly-o-epoxy-N-methylaniline conductive organic carrier comprises the following components by mass percentage: poly-o-epoxy-N-methylaniline conductive adhesive resin 20-25%, polybenzidine curing agent 1-3%, solvent 70-75%, and auxiliary agent 1-2%; The structural monomer of the poly-o-epoxy-N-methylaniline conductive adhesive resin is: Wherein, x is a positive integer between 10 and 200.

2. The high-conductivity paste with low conductive phase filling amount according to claim 1, characterized in that: The poly-o-epoxy-N-methylaniline conductive adhesive resin is prepared by the following method: (1) Under an inert atmosphere, N-methylaniline and persulfate are placed in a hydrochloric acid aqueous solution for polymerization reaction to obtain a desired N-methylaniline polymer; after washing and drying, the polymer is treated with ammonia water to obtain an intrinsic N-methylaniline polymer; (2) dissolving the intrinsic N-methylaniline polymer in a good solvent, adding a halogenated epoxide, and coupling the epoxy group to the aromatic ring of the N-methylaniline polymer under the action of a catalyst to obtain a poly-o-epoxy-N-methylaniline conductive adhesive resin solution; filtering to remove the catalyst and removing the good solvent to obtain the product.

3. The high-conductivity paste with low conductive phase filling amount according to claim 2, characterized in that: In step (2), the ratio of the epoxy group to the aromatic ring is 1:2-10.

4. The high-conductivity paste with low conductive phase filling amount according to claim 2, characterized in that: In step (2), the catalyst is 0.05-0.1 g / mL of anhydrous AlCl3.

5. The highly conductive paste with a low conductive phase filling amount according to claim 2, characterized in that: In step (2), the concentration of the intrinsic N-methylaniline polymer is 0.05-0.5 g / mL, and the concentration of the halogenated epoxide is 0.02-0.1 g / mL.

6. The high-conductivity paste with low conductive phase filling amount according to claim 2, characterized in that: In step (1), the polymerization time is 3 to 10 hours, and the polymerization temperature is 40 to 80°C.

7. The highly conductive paste with a low conductive phase filling amount according to claim 1, characterized in that: The polymerization degree of the polybenzidine curing agent is 3-5.

8. The highly conductive paste with a low conductive phase filling amount according to claim 1, characterized in that: The solvent is at least one of isophorone, butyl carbitol acetate or butyl carbitol.

9. A method for preparing the highly conductive slurry with a low conductive phase filling amount as claimed in claim 1, characterized in that: The following steps are involved: The poly-o-epoxy-N-methylaniline conductive adhesive resin, polybenzidine curing agent, solvent and auxiliary agent are mixed according to mass ratio, and then mixed with silver powder after defoaming and evaporation to obtain the conductive adhesive.

Citation Information

Patent Citations

  • Conductive composition, conductive composition production method, anti-static resin composition and antistatic resin film

    CN104995256A

  • Preparation method and application of high thermal and electrical conductivity adhesive

    CN108102579A